Mass-spectrometric and bioinformatic analysis of eEF1Bγ interactome in the cytoplasmic fraction of A549 cells - Kapustian, L.M.; Lysetsky, I.L.; Bondarchuk, T.V.; Novosylna, O.V.; Negrutskii, B.S. (Інститут молекулярної біології і генетики НАН України, 2018)
Aim. To study protein networks containing the translation elongation factor eEF1B gamma (eEF1Bγ) in lung carcinoma cells. Methods. The protein partners of eEF1Bγ in the cytoplasmic fraction of human lung adenocarcinoma A549 cells were identified by co-immunoprecipitation (co-IP) followed by subsequent liquid chromatography-tandem mass spectrometry (LC-MS/MS). The protein interaction network for eEF1Bγ was determined by a Cytoscape 3.2.0 program using a MCODE plugin. Results. 222 high-scored proteins interacting with eEF1Bγ in the cytoplasm of A549 cells have been identified. Possible functional networks involving these protein-protein interactions were predicted using bioinformatic approaches. Conclusions. Five protein networks were identified as possible targets of eEF1Bγ in lung cancer cells. Apart from translation, eEF1Bγγ was shown to be potentially involved in cell cycle regulation, nucleosome remodeling, transcription, mRNA splicing and processing, and oxidative stress response.